파울러자유자 아메바 감염에 대한 nfa1 유전자백신효과 - Lee, Sang Hee (The Graduate School, Ajou University, 2013)
The pathogenic free-living amoeba, Naegleria fowleri, causes fatal primary amoebic meningoencephalitis in experimental animals and in humans. The nfa1 gene that is cloned from N. fowleri is located on pseudopodia, especially amoebic food-cups and plays an important role in the pathogenesis of N. fowleri. In this study, the retroviral vector (pQCXIN) and the lentiviral vector (pCDH) cloned with the egfp-nfa1 gene was constructed and characterized for nfa1 DNA vaccination in mice. The expression of nfa1 gene in Chinese hamster ovary cell and human primary nasal epithelial cell transfected with the pQCXIN/egfp-nfa1 vector or pCDH/egfp-nfa1 vector was observed by fluorescent microscopy and Western blotting analysis. The viral vector systems effectively delivered the nfa1 gene to the target cells and expressed the Nfa1 protein within the target cells. To evaluate immune responses of nfa1-vaccinated mice, BALB/c mice were intranasally vaccinated with viral particles of each retroviral or lentiviral vector expressing nfa1 gene. DNA vaccination using viral vectors expressing nfa1 significantly stimulated the production of Nfa1-specific IgG subclass, as well as IgG levels. In particular, both levels of IgG2a (Th1) and IgG1 (Th2) were significantly increased in mice vaccinated with viral vectors. The cytokine analysis showed that vaccinated mice elicited stronger IL-4 and IFN-γ production than other control groups, suggesting a Th1/Th2 mixed type immune response. In vaccinated mice, high levels of Nfa1-specific IgG antibody were continued until 12 weeks post-vaccination. The mice vaccinated with viral vector expressing nfa1 gene also exhibited significant higher survival rate (90%) after challenged with N. fowleri trophozoites. The current study shows that the nfa1 vaccination effectively induces protective immunity by humoral and cellular immune response in N. fowleri-infected mice. This is the first report to construct viral vector systems and to evaluate immune responses as DNA vaccination in N. fowleri infection. Furthermore, these results suggest that nfal vaccination may be an effective method for prevention of N. fowleri infection.
학위논문(박사)아주대학교 일반대학원 :의생명학과,2013. 8
Keywords: Naegleria fowleri; nfa1 gene; Retroviral vector; Lentiviral vector; DNA vaccination